PENGARUH SHIFT KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. KAI (Persero) UPT STASIUN TIGA GAJAH BATURAJA - Noviansyah, Noviansyah; Mardiansyah, Mardiansyah; Kurniawan, M (STIE DWI SAKTI BATURAJA, 2024)
This study discusses the effect of shift work and motivation work on performance employees at PT. KAI (Persero) UPT. Stasiun Tigagajah. The data collection technique used in this writing is through the distribution of questionnaires. The total population in this study was 33 people. The analytical method used is a quantitative method using multiple linear regression analysis tools. Based on the results of the analysis that has been carried out, it is concluded that either partially or simultaneously shifts work and motivation work to performance employees at PT. KAI (Persero) UPT. Stasiun Tigagajah. The coefficient of determination (R square) is 0.591. This means that the contribution of the variable effect of reward, punishment, and teamwork on employee performance is 59.1 % while the remaining 4 0.9 % is influenced by other variables not examined in this research, namely responsibility, work discipline and incentives. Keywords: shift work, motivation work, performance employee